ANALISIS PENERAPAN BUKU DINUL ISLAM UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWI KELAS III PONDOK MODERN AL-BAROKAH NGANJUK - Aisa, Aufia; Mahmudah, Lailatul (Universitas KH. A. Wahab Hasbullah, 2021)
This research is motivated by the low reading ability of third grade students at Collage Modern Al-Barokah Nganjuk. This study aims to determine the application of the Islamic Religion book to improve the reading skills of third grade students at Collage Modern Al-Barokah Nganjuk. This type of research uses qualitative research. This research was conducted in class III Collage Modern Al-Barokah Nganjuk. The research subjects were 15 students in class III. This study uses descriptive qualitative data analysis techniques. The results showed an increase in the reading ability of third grade students at Collage Modern Al-Barokah Nganjuk.